Asymmetries and Climate Futures: Working with Waters in an Indigenous Australian Settlement. (September 2019) - Spencer, Michaela; Dányi, Endre; Hayashi, Yasunori
This paper focuses on a water management project in the remote Aboriginal community of Milingimbi, Northern Australia. Drawing on materials and experiences from two distinct stages of this project, we revisit a policy report and engage in ethnographic storytelling in order to highlight a series of sensing practices associated with water management. In the former, a working symmetry between Yolngu and Western water knowledges is actively sought through the practices of the project. However, in the latter, recurrent asymmetries in the research work continue to appear: a bilingual diagram of water usage is displayed but produces confusion; measuring a water hole for salinity, a member of the scientific team throws in a water meter, while a Yolngu elder prefers the telling of an ancestral story; a collaborative 3-D mapping exercise invites participation from community members but struggles to develop an outcome that differs from existing maps used by scientists and government staff. Focusing on these moments as subtle points of rupture, we suggest that attending to "seeing, " "telling, " and "mapping" in both stages of this water management project offers a way to explore the political work of crafting climate futures and beginning to interrogate differing means for "doing difference" within them.